(3eNJGQ TYQ GdTYQGA GdSJIs - (3QhGjI Hh MGJe Sgd Hf eMeO Hf YKeGf Hf jRjO GdLTej GdSLSJGfj Ke GdHUQj (B250 (3g s ((3YHO Gddg Hf GHQGgje GdHYbjdi s)
(3ChdgG (B:s
(3bGd GeQD GdbjS Hf MLQ Hf GdMGQK Hf YeQ Hf MLQ GdCcHQjf YeQh Hf eYGhjI Hf baGfHc ef PcQi MHjH hefRd HSac Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3bGd YfJQI Hf TOGO gd ZGOQ GdTYQGA ef eJQOe Ce gd YQaJ GdPi HYO Jhge s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdTYQGA GdSJ GeQD GdbjS hGdfGHZI , hRgjQ , QhGjI CHj MGJe Yf GdGUeYis
(3QhGjI CHj MGJe Yf GdGUeYis
(3jdjgG cJGH ai GdfMh hdcf GdQWhHI efYJ QDjI GdcJGH s
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs